The Relationship Between Psychological Conditions And Sleep Quality In The Covid-19 Rooms - Widiastuti Widiastuti; Novita Nirmalasari (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: The COVID-19 pandemic has the potential to cause severe psychological harm. Psychological conditions such as anxiety, depression, stress, and disturbances are common among health care workers. The factors causing stress in health workers include workload, fear of being infected with COVID-19, the negative stigma of virus carriers, and being away from family. The research purposed to know the relationship between psychological condition and sleep quality. Methods: The research population consists of all nurses who have worked in the covid room. This research used descriptive correlation with a cross-sectional approach. The samples were collected using a simple random sampling technique with 30 respondents as inclusion and exclusion criteria. The questionnaires Depression Anxiety Stress Scale-21 (DASS-21) and Pittsburgh Sleep Quality Index (PSQI) were completed by the respondent. Data analysis was used Chi-Square. Results: Most of the respondents were females (66,67%) over the age of 30 (70%). Most of them had a nursing education diploma (60%). They were dominant and had normal levels of depression (96,67%), anxiety (86,67%), and stress (93,33%). Most of them had poor sleep quality (63,33%). According to the findings, the p-values for depression, anxiety, and stress in sleep quality were 0.43, 0.73, and 0.26. It represents that no relationship exists between one variable and another. Meanwhile, some respondents have mild depression, moderate anxiety, and mild stress with poor sleep quality. Conclusion: Poor psychological conditions are still found in nurses, which can interfere with the quality of nursing services. Additional nursing interventions are required to improve nurses' psychological well-being.